DANA BOS DAN PEMERATAAN LAYANAN PENDIDIKAN DASAR - Dawous Gilang Gumilang; Silvi Setya Oktaviany; Moch Rizky Ashari (Jurnal Al Burhan, 2022)
The government has now provided Bantuan Operasioanl Sekolah (BOS) program in the form of a budget allocated for teaching and learning activities in basic education units. The purpose of the BOS funding program is to improve the quality of learning and equal access to education services. BOS funding that uses the FLAT GRANT model as a Financing Model makes the equitable distribution of education services have gaps, especially in 3T (Terdepan, Terpencil dan Tertinggal) areas. Flat grants calculated based on the number of students make schools that have few students somewhat hampered in managing budgets. What's more, with difficult access to education, limited resources, the behavior of people who do not fully understand the benefits of schooling and the cost of expensive needs in the 3T area. So local governments must be more concerned about policy, planning, access, distribution, use, accountability and reporting that must be sustainable. This continuity is important in the management of education costs, so that the better the management of education costs, the better the output of schools as the productivity of a nation.